COLLAGEN ANALYSIS OF GRAFT IN BONE TUNNEL MODEL ANTERIOR CRUCIATE LIGAMENT (ACL) RECONSTRUCTION WITH INTRATUNNEL ALLOGENIC BONE MARROW MESENCHYMAL STEM CELLS (MSCs) AND VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) - petrasama, petrasama (Journal of Stem Cell Research and Tissue Engineering, 2018)
ACL reconstruction measures aim to obtain stable knees, and reduce the risk of further injury to the meniscus and joint surfaces. Acceleration of the integration process between the tendon graft and the bone tunnel will improve the final result of ACL reconstruction. The purpose of this study was to investigate the collagen composition of the bone tunnel graft model of anterior cruciate ligament reconstruction with intravenous allogenic bone marrow mesenchymal stem cells and vascular endothelial growth factor in experimental animals. The design of this study was Post-test only Control Group Design using 20 rabbits divided into treatment group and control group. Collagen immunohistochemical evaluation was performed at weeks 3 and 6. Evaluation at week 3 obtained the area of collagen type-1 in the higher treatment group at treatment (p <0.001). In the 6th week evaluation, it was found that the area of collagen type-1 in the treatment group was higher (p <0.05). Type-1 collagen at week 6 did not differ significantly with week 3 (p> 0.05). Provision of allogenic bone marrow mesenchymal stem cells and intratonal vascular endothelial growth factor in ACL reconstruction enhanced the formation of collagen type-1 which is the acceleration of incorporation of the graft tendon process with bone tunnel.Keywords : Anterior Cruciate Ligament, allogenic bone marrow mesenchymal stemcells, vascular endothelial growth factor, graft and collagen.